QUALITY ASSESSMENT OF HYBRID MAIZE SEEDS ACCORDING TO THEIR SHAPE AND SIZE - Tabakovic, Marijenka (Journal on Processing and Energy in Agriculture, 2021)
Maize seed is characterised by a variety of shapes and sizes, which directly or indirectly affect physiological properties. The aim of the present study was to establish the significance of the seed shape and size on the first count and germination.  The following eight hybrids were used as a seed material in the trial: ZP196, ZP260, ZP341, ZP360, ZP434, ZP677, ZP684 and ZP704. The traits of seed shape and size were observed under laboratory conditions. The seed weight, the first count and germination were determined. The traits genotype and the fraction significantly affected seed formation (R≥0.900), while the significance of these factors for the first count and germination was small (R≤0.09). The first count and germination was high (above 95%) in all sizes and all shapes of seeds. The lowest first count and germination were detected in SO (94.2; 95.1, respectively), while the highest values were determined in SSP (97.1; 98.0, respectively).
Keywords: seed, physical properties, uniformity